PEMETAAN SEBARAN DAN KERAPATAN MANGROVE MENGGUNAKAN METODE SVM DAN ANALISIS NDVI DENGAN CITRA SENTINEL-2A DI DESA BUSUNG PANJANG: Mangrove Distribution and Density Mapping Using SVM and NDVI with Sentinel-2A Imagery in Busung Panjang Village - Muhammad Alwie Nasution; Esty Kurniawati; Falmi Yandri (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2026)
Mangrove ecosystems have important ecological and economic roles; however, their existence is vulnerable to changes caused by human activities. This study aimed to map the distribution and density of mangrove ecosystems in Busung Panjang Village, Kepulauan Posek District, Lingga Regency using Sentinel-2A imagery from 2018 and 2023. The methods used included Support Vector Machine (SVM) classification for land cover identification and Normalized Difference Vegetation Index (NDVI) analysis to determine mangrove density levels. Field data were collected using a stratified random sampling method with a total of 170 sample points used for classification and accuracy assessment. The results showed that the SVM classification produced an accuracy level of 83.33% in 2018, which increased to 96.67% in 2023. NDVI analysis showed that mangrove density in the study area was dominated by the dense category, covering 21.30 Ha in 2018 and increasing to 29.74 Ha in 2023. Validation between NDVI results and field data showed a conformity level of 88%. These findings indicate that Sentinel-2A imagery combined with SVM and NDVI methods can provide reliable information on mangrove distribution and density as a basis for sustainable mangrove ecosystem management.